2017
DOI: 10.1016/j.envint.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Manganese in teeth and neurobehavior: Sex-specific windows of susceptibility

Abstract: Background Manganese (Mn) is an essential element required for growth and development, but higher body burdens have been associated with neurobehavioral decrements in children. Objectives We examined whether prenatal or postnatal Mn measured in deciduous teeth was associated with scores on a test of visuospatial learning and memory. Methods Deciduous teeth were collected from 142 participants (ages 10–14 years) residing near varied ferro-manganese industry in Italy. Mn concentrations were measured in prena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 77 publications
(139 reference statements)
5
46
0
Order By: Relevance
“…These results suggested that Mn associations were partly driven by exposure timing and modified by sex. Three studies also found that tooth Mn concentrations were higher in the prenatal than postnatal period [42,48,55], indicating a greater demand for manganese in the prenatal period. No significant associations were observed between neurodevelopmental outcomes and Mn in saliva, toe nail [8], and urine [60] (see Table 2).…”
Section: Manganese In Biomarkers and Neurodevelopmental Outcomesmentioning
confidence: 98%
“…These results suggested that Mn associations were partly driven by exposure timing and modified by sex. Three studies also found that tooth Mn concentrations were higher in the prenatal than postnatal period [42,48,55], indicating a greater demand for manganese in the prenatal period. No significant associations were observed between neurodevelopmental outcomes and Mn in saliva, toe nail [8], and urine [60] (see Table 2).…”
Section: Manganese In Biomarkers and Neurodevelopmental Outcomesmentioning
confidence: 98%
“…In addition to the sex-specific difference in thyroid follicle size in Slc30a10 +/+ versus Slc30a10 KO/KO mice, we also observed sex-specific differences in biliary copper levels and bile flow rates ( Figure 5, E and G). Although some of this may be attributed to intra-sex variability, other studies have reported sex-specific differences in Mn levels in individuals living near ferro-Mn industries, in rats fed diets deficient or adequate in Mn, and in children with polymorphisms in Mn transporters (26,40,41). More research is required to understand the impact of sex on metal homeostasis in health and disease.…”
Section: Volume 129 Number 12 December 2019mentioning
confidence: 99%
“…In a longitudinal assessment in this area, higher levels of Mn in drinking water, but not hair Mn, were associated with lower Performance IQ in girls, whereas the opposite was observed in boys (Dion et al, 2018). Evidence of sex-specific neurodevelopmental effects of Mn were presented at the conference also for motor functions (Chiu et al, 2017), visuospatial ability (Bauer et al, 2017). Teeth Mn reflecting early life exposure resulted a significant predictor for the same motor functions (Chiu et al, 2017) and visuospatial ability (Bauer et al, 2017), and Mn concentrations in dentine was influenced by common SNPs of Mn transporter genes SLC30A10 and SLC39A8, with sex differences (Wahlberg et al, 2018).…”
Section: Scientific Advances Reported At the Conferencementioning
confidence: 98%
“…Evidence of sex-specific neurodevelopmental effects of Mn were presented at the conference also for motor functions (Chiu et al, 2017), visuospatial ability (Bauer et al, 2017). Teeth Mn reflecting early life exposure resulted a significant predictor for the same motor functions (Chiu et al, 2017) and visuospatial ability (Bauer et al, 2017), and Mn concentrations in dentine was influenced by common SNPs of Mn transporter genes SLC30A10 and SLC39A8, with sex differences (Wahlberg et al, 2018). Finally, coexposure to Mn and depression during pregnancy was shown as having an impact on developmental Bayley scores among the children at 24 months of age (Munoz-Rocha et al, 2018).…”
Section: Scientific Advances Reported At the Conferencementioning
confidence: 98%